Fecal microbiota changes in NZB/W F1 mice after induction of lupus disease - Yen-Fu Chen; Ao-Ho Hsieh; Lian-Chin Wang; Yun-Ju Huang; Yun-Chen Tsai; Wen-Yi Tseng; Yu-Lun Kuo; Shue-Fen Luo; Kuang-Hui Yu; Chang-Fu Kuo (Scientific Reports, 2021)
Abstract The association between the gut microbiota and the development of lupus is unclear. We investigated alterations in the gut microbiota after induction of lupus in a murine model using viral peptide of human cytomegalovirus (HCMV). Three treatment arms for the animals were prepared: intraperitoneal injection of HCMVpp65 peptide, adjuvant alone, and PBS injection. Feces were collected before and after lupus induction biweekly for 16S rRNA sequencing. HCMVpp65 peptide immunization induced lupus-like effects, with higher levels of anti-dsDNA antibodies, creatinine, proteinuria, and glomerular damage, compared with mice treated with nothing or adjuvant only. The Simpson diversity value was higher in mice injected with HCMVpp65 peptide, but there was no difference in ACE or Chao1 among the three groups. Statistical analysis of metagenomic profiles showed a higher abundance of various families (Saccharimonadaceae, Marinifiaceae, and Desulfovibrionaceae) and genera (Candidatus Saccharimonas, Roseburia, Odoribacter, and Desulfovibrio) in HCMVpp65 peptide-treated mice. Significant correlations between increased abundances of related genera (Candidatus Saccharimonas, Roseburia, Odoribacter, and Desulfovibrio) and HCMVpp65 peptide immunization-induced lupus-like effects were observed. This study provides insight into the changes in the gut microbiota after lupus onset in a murine model.